2021
DOI: 10.1177/1056789520986601
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling of plain and reinforced concrete specimens with the Kotsovos and Pavlovic material model, smeared crack approach and fine meshes

Abstract: Modelling of concrete through 3 D constitutive material models is a challenging subject due to the numerous nonlinearities that occur during the monotonic and cyclic analysis of reinforced concrete structures. Additionally, the ultimate limit state modelling of plain concrete can lead to numerical instabilities given the lack of steel rebars that usually provide with the required tensile strength inducing numerical stability that is required during the nonlinear solution procedure. One of the commonly used 3 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…A similar approach will be used, and adjustments will be made where needed to model the RC waffle slabs that are bare or retrofitted with CFRP plates. It is important to note here that Reconan FEA was validated through the use of experimental results as presented in [5][6][7][8].…”
Section: Methodsmentioning
confidence: 99%
“…A similar approach will be used, and adjustments will be made where needed to model the RC waffle slabs that are bare or retrofitted with CFRP plates. It is important to note here that Reconan FEA was validated through the use of experimental results as presented in [5][6][7][8].…”
Section: Methodsmentioning
confidence: 99%
“…Modelling in 3D considers the effect of out-of-plane stresses, where the stressstrain relationship for each stress-state is expressed by the hydrostatic (σ 0 ) and deviatoric components (τ 0 ) ( Markou & Roeloffze 2021). The recent research work presented by describes how the corresponding hydrostatic and deviatoric strains (ε 0 , γ 0 ) are used to produce the hydrostatic and deviatoric stresses, by using a material model proposed by Kotsovos and Pavlovic (1995) and extended by Markou and Papadrakakis (2013).…”
Section: Modelling Of Concrete and Soil Materialsmentioning
confidence: 99%
“…For this reason, the FEM-based software (ReconanFEA 2020) is used for the needs of this research work. Furthermore, by analysing numerical models under different loading conditions and using a variety of meshes, it can be determined if the structural design is safe or not (Markou & Roeloffze 2021). Modelling of piles embedded in soil was performed by , where experimental and numerical results showed that ReconanFEA (2020) has the ability to objectively capture the mechanical response of this complex problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach can lead to excessive cracking in order to represent a severely damaged state. Although the model doesn't appear to have mesh sensitivity issues [10], it is difficult to prove with the current algorithmic approach. To control the smeared cracking, a crack band approach [11] must be applied.…”
Section: Introductionmentioning
confidence: 99%